Cochlear Histopathologic Findings in Patients With Systemic Lupus Erythematosus: A Human Temporal Bone Study. Issue 5 (June 2016) - Kariya, Shin; Kaya, Serdar; Hizli, Ömer; Hizli, Pelin; Nishizaki, Kazunori; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Supplemental Digital Content is available in the text Abstract : Hypothesis: We hypothesized that, in archived human temporal bone samples from patients with systemic lupus erythematosus (SLE), a pathologic condition exists in the stria vascularis and cochlear hair cells. Background: Sensorineural hearing loss is a common feature in SLE patients. However, the pathophysiologic mechanism of cochlear dysfunction is unclear. Methods: We examined 15 temporal bone samples from 8 SLE patients, along with 17 samples from 10 age-matched healthy control patients. The samples were serially sectioned in the horizontal plane and stained with hematoxylin and eosin. We determined the area of the stria vascularis in a midmodiolar section of each cochlear turn. Then, we made cytocochleograms and calculated the percentage of missing inner and outer hair cells. Results: The area of the stria vascularis in our SLE group was significantly smaller than in our control group. The number of remaining inner hair cells in our SLE group was smaller than in our control group; however, the difference did not reach statistical significance. The loss of outer hair cells in our SLE group was significantly higher than in our control group. There was a tendency toward a positive correlation between the loss of cochlear hair cells and the duration of SLE. Conclusion: The stria vascularis and cochlear hair cells are affected in SLE patients. Our findings could provide the histopathologic basis for the cochlear dysfunction, including sensorineural hearing loss, experienced by SLE patients.